IMPORTANCE OF MOTHER TONGUE IN CONDITION OF FORMING TRILINGUALISM - Kappazova, Sh.T.; Utegenova, B.M. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article examines the role of mother tongue in trilingual education and its importance in the formation of a person. At the same time, the problems of trilin-gualism on the ethnology of each population, the problems of trinity in school have been analyzed.
Keywords: trilingualism; native language; foreign language; Russian language; traditions; people